Martin Luther and the seven sacraments: a contemporary Protestant reappraisal - Brewer, Brian C. ca. 20./21. Jh. (Baker Academic, a division of Baker Publishing Group, 2017)
Penance: the once third Protestant sacrament -- Confirmation: a ceremony for the laying on of hands -- Marriage: a public ordinance -- Ordination: "a man-made fiction" -- Extreme unction: "anointing the sick" -- Baptism: the "untouched and untainted" sacrament -- The Lord's Supper: "the most important of all